Prototype of Solar Cell Automatic Charging Handphone as Alternative Sources of Electricity - Bagus Ageng Purwibawa; Saidah (JEECS (Journal of Electrical Engineering and Computer Sciences), 2022)
Electrical energy has not been able to adequately meet the needs of communication equipment in the remote areas,especially at a location far from electrical energy sources such as when conducting natural tourism, traveling to thebeach or doing mountain climbing. Utilizing solar cell as an alternative source of electrical energy will support themanufacture of automatic charger equipment that will be supplied to the load of handphone where the method used inthe charging process is constant current and constant voltage.This method uses LM317 as its main component. Thedesign of this tool uses two 3000 mAh capacity batteries that are assembled in parallel.Where the battery is flowingcurrent and voltage constantly so as not to happen overcharging.The circuit is controlled automatically using theArduino nano and is monitored via LCD.